Degradasi Moral Remaja Muslim di Era Media Sosial dalam Perspektif Pendidikan Islam - Hamidiyah, Shafa Aulia; Aripin, Syamsul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This qualitative-descriptive study examines, from an Islamic education perspective, the moral decline of Muslim youth caused by uncontrolled social media use. The findings indicate a diminished sense of shame, impulsiveness, and a decline in spirituality are the main consequences. Weak religious understanding, lack of family support, and pressures from the digital world are underlying causes. Islamic education is integrated as a preventive and curative tool by instilling moral values, highlighting positive role models, and promoting Islamic digital literacy. This study underscores the urgent need for cross-sector collaboration to strengthen the moral resilience of youth in the digital age.